Multiple Sclerosis: Current Knowledge of the Pathology and Use of Monoclonal Antibodies as a Promising Therapy - Castellón-Arias, Josué; Gazel-Meléndez, Luana; Guido-Villalobos, Rebeca; Jiménez-Díaz, Ariela; Valera-Rangel, Johana; Mora-Román, Juan José (Borneo Journal of Pharmacy, 2023)
Multiple sclerosis is an autoimmune condition characterized by an inflammatory condition and neuron demyelination, leading to a significant deterioration in the patient's quality of life as the disease progresses. The immune system reactivity in this pathology is mainly mediated by reactive T lymphocytes against myelin. The harmful substances production and proinflammatory cell infiltration occur. Currently, there is no cure, so treatment focuses on reducing the development of the individual's long-term disability by addressing symptoms, acute exacerbations, and slowing progress. The traditional treatment includes immunosuppressive substances such as corticosteroids and interferons. However, an approach to more specific, highly effective therapies such as monoclonal antibodies is currently being sought. Ofatumumab, ocrelizumab, alemtuzumab, and rituximab are commercialized monoclonal antibodies. Likewise, therapies in the research phase, such as ublituximab, inebilizumab, GNbAC1, and elezanumab, can be found. Therefore, research must continue to have more information to increase the availability of therapeutic options for patients.